Judgement and Truth in Early Analytic Philosophy and Phenomenology
X, 275 p.
Keywords: What is judgement? is a question that has exercised generations of philosophers. Early analytic philosophers (Frege, Russell and Wittgenstein) and phenomenologists (Brentano, Husserl and Reinach) changed how philosophers think about this question. This book explores and assesses their contributions and help us to retrace their steps.